Pengaruh Pendidikan dan Pelatihan Terhadap Prestasi Kerja Pegawai Kantor Dinas Komunikasi dan Informatika Provinsi Sumatera Utara - Iriani Iriani; Julkarnain Julkarnain; M Dwiza Johanda Putra (Universitas Nusantara PGRI Kediri, 2023)
The problem in this thesis is that employees rarely participate in education and training programs so that it has an influence on employee performance. The purpose of this study was to determine and analyze the effect of education on the work performance of the employees of the Communication and Informatics Service of North Sumatra Province, to determine and analyze the effect of training on the work performance of the employees of the North Sumatra Province of Communication and Information Technology, to determine and analyze the effect of education and training on work performance of employees of the Department of Communication and Information Technology of North Sumatra Province. Based on the results of the study, it is known that there is a positive influence of the education variable on the work achievement variable. There is a positive effect of the training variable on the work achievement variable. Education and training simultaneously have an influence on employee performance.